2022
DOI: 10.1186/s12929-022-00839-6
|View full text |Cite
|
Sign up to set email alerts
|

Gut microenvironmental changes as a potential trigger in Parkinson’s disease through the gut–brain axis

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease attributed to the synergistic effects of genetic risk and environmental stimuli. Although PD is characterized by motor dysfunction resulting from intraneuronal alpha-synuclein accumulations, termed Lewy bodies, and dopaminergic neuronal degeneration in the substantia nigra, multiple systems are involved in the disease process, resulting in heterogenous clinical presentation and progression. Genetic predisposition to PD regarding aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 195 publications
0
20
0
Order By: Relevance
“…EECs, ECCs, and the mucosal immune system interact with several microbial metabolites, including as SCFAs, LPS, secondary bile acids, and tryptophan metabolites, to mediate communication between the gut and the brain. Some of these metabolites, however, may also cross the BBB and make their way into the brain via the BBB after passing through the intestinal barrier. ,, Blood is the medium through which neuroactive substances produced by microbes can be distributed throughout the body and trigger a signaling response. As host signaling molecules, SCFAs regulate the production of tight junction proteins including zonula occludens (ZO)-1 and claudin-1 to keep intestinal epithelial cells functional.…”
Section: Various Signaling Pathways Involved In Propagation Of α-Syn ...mentioning
confidence: 99%
See 2 more Smart Citations
“…EECs, ECCs, and the mucosal immune system interact with several microbial metabolites, including as SCFAs, LPS, secondary bile acids, and tryptophan metabolites, to mediate communication between the gut and the brain. Some of these metabolites, however, may also cross the BBB and make their way into the brain via the BBB after passing through the intestinal barrier. ,, Blood is the medium through which neuroactive substances produced by microbes can be distributed throughout the body and trigger a signaling response. As host signaling molecules, SCFAs regulate the production of tight junction proteins including zonula occludens (ZO)-1 and claudin-1 to keep intestinal epithelial cells functional.…”
Section: Various Signaling Pathways Involved In Propagation Of α-Syn ...mentioning
confidence: 99%
“…27,28 Abnormal neurotransmitters are released as a result of altered microtubule function and dysfunction of the presynaptic terminal of neurons. 29 2.2. Alteration in the Digestive System.…”
Section: Pathophysiology Associated With Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota is involved in the metabolism of polyunsaturated fatty acids (PUFAs). Metabolites of PUFAs are increased in the gut of AD patients and modulate microglial activation in the brain [46] . R13 exerts its therapeutic efficacy on AD both by directly activating TrkB and restoring normal constituents of the gut microbiota.…”
Section: The Gut-brain Axismentioning
confidence: 99%
“…Pathogenic α-syn was found in both enteroendocrine cells and intestinal neurons. It could reach the brain from the intestine through the vagus nerve and cause pathological changes in the central nervous system (Holmqvist et al, 2014;Chen and Lin, 2022). The study found that pathogenic α-syn was injected into the duodenum and pylorus muscle layer in mice produced symptoms similar to those of PD and successively in the vagus nerve dorsal motor nucleus, after brain tail, the basolateral amygdala, dorsal raphe nucleus and substantia nigra compacta found pathogenic α-syn, and cut off the vagus nerve can inhibit the occurrence of this phenomenon (Kim et al, 2019).…”
Section: Gut Microbiota Directly Stimulates Production Of Pathogenic ...mentioning
confidence: 99%